Antibacterial Activity of Ethanol Extract of Dragon’s Blood (Daemonorops didymophylla) Against Salmonella typhi and Streptococcus mutants. - Minarni - Minarni (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2020)
Abstract. Dragon’s blood is essentially a red-colored resin secreted by the fruits of rattan species. Dragon’s blood originated from Indonesia which becomes widespread in the international market is indigenous from Daemonorops sp. Dragon’s blood has been popularly used as traditional medicines. The benefit of dragon’s blood as medicine certainly cannot be separated from the content of secondary metabolites. To confirm such dragon’s blood efficacy, an assessment was already conducted regarding the phytochemical screening and activity dragon’s blood produced by three rattan species, i.e. Daemonorops didymophylla. Ethanol extract of dragon’s blood contains secondary metabolites which are effective as an antibacterial against Salmonella typhi and Streptococcus mutants. This study aims to determine what are the classes of compounds contained in the ethanol extract of dragon’s blood Daemonorops didymophylla which is effective as an antibacterial against the bacteria Salmonella typhi and Streptococcus mutants. Results revealed that the separation of the active compound ethanol extract of dragon’s blood Daemonorops didymophylla, where the separation of compounds through liquid vacuum chromatography has 4 combined fractions. The class of compounds found in the ethanol extract of dragon’s blood Daemonorops didymophylla are flavonoids, triterpenoids and alkaloids. Antibacterial activity of Daemonorops didymophylla dragon’s blood ethanol extract against Salmonella typhi and Streptococcus mutans showed that the higher the concentration the higher the inhibitory power produced, for Salmonella typhi in the 1000 ppm extract obtained an inhibition zone of 13.63 mm with a strong category while Streptococcus mutans in the 1000 ppm extract obtained a inhibition zone of 11.86 mm with a strong category and fraction 1 is the fraction that has the largest inhibition zone than the other three fractions with a large inhibition zone of 14.6 mm in testing Salmonella typhi and 12.1 mm in testing Streptococcus mutants.